Antimicrobial stewardship situation analysis in selected hospitals in Zambia: findings and implications from a national survey - Joseph Yamweka Chizimu; Joseph Yamweka Chizimu; Steward Mudenda; Kaunda Yamba; Chileshe Lukwesa; Raphael Chanda; Ruth Nakazwe; Bwalya Simunyola; Misheck Shawa; Misheck Shawa; Aubrey Chichonyi Kalungia; Duncan Chanda; et al. (Frontiers Media S.A., 2024)
BackgroundAntimicrobial stewardship (AMS) programs are critical in combating antimicrobial resistance (AMR). In Zambia, there is little information regarding the capacity of hospitals to establish and implement AMS programs. The objective of this study was to conduct a baseline assessment of WHO core elements for an AMS program implementation in eight hospitals in Zambia.Materials and methodsWe conducted an exploratory cross-sectional study from September 2023 to December 2023 using a self-scoring Periodic National and Healthcare Facility Assessment Tool from the World Health Organization (WHO) policy guidance on integrated AMS activities in human health. Eight public hospitals were surveyed across the five provinces of Zambia. Data was analyzed using the WHO self-scoring tool and thematic analysis.ResultsOverall, 62.5% (6/8) of the facilities scored low (below 60%) in implementing AMS programs. Most facilities had challenges with reporting AMS feedback within the hospital (average score = 46%), Drugs and Therapeutics Committee (DTC) functionality (average score = 49%), AMS actions (average score = 50%), education and training (average score = 54%), and leadership commitment to AMS activities (average score = 56%). The overall score for all AMS core elements was average (56%). All the hospitals (100%) did not have an allocated budget for AMS programs. Finally, there were neither antibiograms to guide antimicrobial utilization nor AMS-trained staff in more than 50% of the hospitals surveyed.ConclusionThis study found low AMS implementation in these public hospitals, especially where DTCs were non-functional. The identified challenges and gaps require urgent attention for sustainable multidisciplinary AMS programs.